2020
DOI: 10.1002/mbo3.1093
|View full text |Cite
|
Sign up to set email alerts
|

Vibrios from the Norwegian marine environment: Characterization of associated antibiotic resistance and virulence genes

Abstract: A total of 116 Vibrio isolates comprising V. alginolyticus (n = 53), V. metschnikovii (n = 38), V. anguillarum (n = 21), V. antiquarius (n = 2), and V. fujianensis (n = 2) were obtained from seawater, fish, or bivalve molluscs from temperate Oceanic and Polar Oceanic area around Norway. Antibiotic sensitivity testing revealed resistance or reduced susceptibility to ampicillin (74%), oxolinic acid (33%), imipenem (21%), aztreonam (19%), and tobramycin (17%). Whole‐genome sequence analysis of eighteen drug‐resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
30
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 83 publications
6
30
3
Order By: Relevance
“…The overall results from our study are in accordance with previous studies on AMR in bacteria from the Norwegian marine environment, where low prevalence of acquired resistance was found in E. coli and Vibrio spp. [22,60,61]. In the present study, acquired resistance was only found in few K. pneumoniae isolates and in none of the other isolated species.…”
Section: Discussioncontrasting
confidence: 53%
“…The overall results from our study are in accordance with previous studies on AMR in bacteria from the Norwegian marine environment, where low prevalence of acquired resistance was found in E. coli and Vibrio spp. [22,60,61]. In the present study, acquired resistance was only found in few K. pneumoniae isolates and in none of the other isolated species.…”
Section: Discussioncontrasting
confidence: 53%
“…However, the eaeA gene and fasA gene may play a major role in adherence/colonization, causing attaching/effacing lesions (Rehman et al, 2017;Stromberg et al, 2020). The emergence of virulence gene patterns observed in the current study might be due to horizontal gene transfer mediating transfer virulence factors (Håkonsholm et al, 2020).…”
Section: Discussionmentioning
confidence: 66%
“…Vibrio metschnikovii is ubiquitous in water (both salty and fresh), particularly in 2020, 38 species of Vibrio metschnikovii were selected from the Norwegian Sea nearby the Norwegian coast and from the herring fish of the same Sea 7 . Vibrio metschnikovii is associated with the ability to cause human diseases, mostly diarrhea, skin infections, and bacteremia; otherwise, some authors say that Vibrio metschnikovii induce only extraintestinal symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Also, this pathogen was found in the chicken's intestines and together with E. coli caused hepatitis 10 . 38 strains indicated nearby the Norwegian seashore had the genes of resistance adeF (responsible for polypharmacological efflux mechanism), blaCARB (responsible for carbenicillin resistance), catB‐related (responsible for chloramphenicol resistance), and genes that are responsible for pathogenicity factors Hem III (hemolysin type III), hylA, tlh 7 . Usually, the pathogen has huge plasmids (190‐340 кB), but their function is not exactly known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation